The Gospel according to Jesus What is Authentic Faith? - MacArthur, John (Grand Rapids Zondervan, 2008)
Discusses ways that people can live according to Jesus' own ministry, presenting challenging questions for Christians who wish to reevaluate their commitment to Jesus as Lord and Savior.
Keywords: Jesus Christ -- Person and offices. Jesus Christ. Christian life. Christology